A novel flow field with controllable pressure gradient to enhance mass transport and water removal of PEM fuel cells. Issue 6 (27th February 2020) - Xing, Lei; Xu, Yuanxiang; Penga, Željko; Xu, Qian; Su, Huaneng; Shi, Weidong; Barbir, Frano
Abstract: An easily machined novel flow field with controllable pressure gradient across adjacent channels was designed and a two dimensional, across‐the‐channel, two‐phase model was developed to study the gas transport and water removal of the novel configuration. The effect of channel‐rib width ratio, GDL thickness and pressure gradient on the profiles of oxygen concentration and water saturation within the GDL were investigated. Special attention was paid to the mechanisms of the promoted mass transport and water removal rates under a pressure gradient. The model was validated by experiments with various channel‐rib ratios and GDL thicknesses at different operating pressure. The results revealed that, oxygen concentration was increased, and the water saturation was reduced under the rib with a pressure gradient generated across the adjacent channels. The optimal pressure gradient is between 0.1 to 0.2 atm for the studied channel geometry and configuration. The mechanisms of the improved cell performance were elucidated.